Efficacy and safety of upadacitinib in patients with active ankylosing spondylitis (SELECT-AXIS 1): a multicentre, randomised, double-blind, placebo-controlled, phase 2/3 trial. Issue 10214 (7th December 2019) - van der Heijde, Désirée; Song, In-Ho; Pangan, Aileen L; Deodhar, Atul; van den Bosch, Filip; Maksymowych, Walter P; Kim, Tae-Hwan; Kishimoto, Mitsumasa; Everding, Andrea; Sui, Yunxia; Wang, Xin; Chu, Alvina D; et al.
Summary: Background: The JAK pathway is a potential therapeutic target in ankylosing spondylitis. This study assessed the efficacy and safety of upadacitinib, a selective JAK1 inhibitor, in patients with ankylosing spondylitis. Methods: This multicentre, randomised, double-blind, placebo-controlled, two-period, parallel-group, phase 2/3 study, SELECT-AXIS 1, enrolled adults in 62 sites in 20 countries. Eligible patients had active ankylosing spondylitis, fulfilled modified New York criteria, were previously untreated with biological disease-modifying antirheumatic drugs, and had inadequate response to at least two or intolerance or contraindication to non-steroidal anti-inflammatory drugs. Patients were randomly assigned 1:1 using interactive response technology to take oral upadacitinib 15 mg once daily or oral placebo for the 14-week period 1; only period 1 data are reported here. The primary endpoint was the composite outcome measure of the Assessment of SpondyloArthritis international Society 40 response at week 14. Analyses were done in the full analysis set of patients who were randomly assigned and received at least one dose of study drug. This study is registered with ClinicalTrials.gov, NCT03178487 . Findings: Between Nov 30, 2017, and Oct 15, 2018, 187 patients were randomly assigned to upadacitinib 15 mg (93 patients) or to placebo (94 patients), and 178 (95%) patients (89 in the upadacitinib group and 89 in the placebo group) completed period 1 on study drug (by the completion date of Jan 21, 2019). Significantly more patients had an Assessment of SpondyloArthritis international Society 40 response in the upadacitinib group versus in the placebo group at week 14 (48 [52%] of 93 patients vs 24 [26%] of 94 patients; p=0·0003; treatment difference 26% [95% CI 13–40]). Adverse events were reported in 58 (62%) of 93 patients in the upadacitinib group versus 52 (55%) of 94 in the placebo group. The most common adverse event in the upadacitinib group was increased creatine phosphokinase (eight [9%] of 93 patients in the upadacitinib group vs two [2%] of 94 patients with placebo). No serious infections, herpes zoster, malignancy, venous thromboembolic events, or deaths were reported; one serious adverse event was reported in each group. Interpretation: Upadacitinib 15 mg was efficacious and well tolerated in patients with active ankylosing spondylitis who had an inadequate response or contraindication to non-steroidal anti-inflammatory drugs. These data support the further investigation of upadacitinib for the treatment of axial spondyloarthritis. Funding: AbbVie.